Psycology: themes and variations - Weiten, Wayne (Wadsworth, 2002)
Contiene: The evolution of psycology. The research enterprise in psychology. The biological bases of bahavior. Sensation and perception. Variations in consciousness. Learning. Human memory. Lenguage and thought. Intelligence and psychological testing. Motivation and emotion. Human development across the life span. Personality: theory, research, and assessment. Stress, coping, and health. Psychological disorders. Treatment of psichological disorders. Social behavior
Keywords: Psicología